A investigação sobre cerâmica castreja no Norte de Portugal - Soeiro, Teresa (2020)
A bibliographic perspective through significant views and research works on castreja ceramics in Northern Portugal, since Martins Sarmento time until the 21st century, emphasizing the chronotypological propositions and the transitions.